Study of the early management of acute pancreatitis. Issue 10 (24th September 2015) - Nesvaderani, Maryam; Eslick, Guy D.; Faraj, Shadi; Vagg, Daniel; Cox, Michael R.
Abstract: Background: Acute pancreatitis (AP) is a common acute surgical presentation with evidence‐based guidelines for early management. The aim of this study was to assess the compliance to the published guidelines in patients presenting with AP in Western Sydney. Methods: A retrospective case note audit was conducted for all patients with a confirmed diagnosis of AP from 2008 to 2011 in Western Sydney. Results: There were 932 patients. The mortality was low for mild (0.7%) and severe (1.2%) AP. There was an under‐utilization of ultrasound (U/S) with 239 (25.6%) patients not having a U/S. There was an over‐utilization of early (within 72 h) computed tomography scanning for diagnosis (31.1%), assessment of severity (16.1%) and assessment for the presence of complications (7.3%). Inappropriate prophylactic antibiotic usage occurred in 15.3% patients. Of 373 cases of gallstone pancreatitis, only 231 (69.1%) had a cholecystectomy within 4 weeks of presentation. There was an under‐utilization of early endoscopic retrograde cholangiopancreatography for associated cholangitis (12.5%). Only 16 (18.8%) patients with severe pancreatitis received enteric feeding. In patients with pancreatic necrosis, 50% had invasive intervention delayed beyond 4 weeks and 69% had minimally invasive procedures performed prior to necrosectomy. Patients having a minimally invasive procedure initially showed an improvement in mortality compared with those who had primary necrosectomy (0 versus 40%, P = 0.025). Conclusions: Although morbidity and mortality were acceptable, there was a failure to comply with evidence‐based guidelines for the early management of pancreatitis. The results support for the development and auditing of protocols for the early assessment and treatment of AP in all hospitals.